Bazooka mediates secondary axon morphology in Drosophila brain lineages - Hartenstein Volker; Spindler Shana R (Neural Development, 2011)
Abstract In the Drosophila brain, neural lineages project bundled axon tracts into a central neuropile. Each lineage exhibits a stereotypical branching pattern and trajectory, which distinguish it from other lineages. In this study, we used a multilineage approach to explore the neural function of the Par-complex member Par3/Bazooka in vivo. Drosophila bazooka is expressed in post-mitotic neurons of the larval brain and localizes within neurons in a lineage-dependent manner. The fact that multiple GAL4 drivers have been mapped to several lineages of the Drosophila brain enables investigation of the role of Bazooka from larval to adult stages Bazooka loss-of-function (LOF) clones had abnormal morphologies, including aberrant pathway choice of ventral projection neurons in the BAla1 lineage, ectopic branching in the DALv2 and BAmv1 lineages, and excess BLD5 lineage axon projections in the optic medulla. Exogenous expression of Bazooka protein in BAla1 neurons rescued defective guidance, supporting an intrinsic requirement for Bazooka in the post-mitotic neuron. Elimination of the Par-complex member Par6 recapitulated Bazooka phenotypes in some but not all lineages, suggesting that the Par complex functions in a lineage-dependent manner, and that Bazooka may act independently in some lineages. Importantly, this study highlights the potential of using a multilineage approach when studying gene function during neural development in Drosophila.